Landforms contribute to plant biodiversity at alpha, beta and gamma levels. (10th April 2019) - Tukiainen, Helena; Kiuttu, Mikko; Kalliola, Risto; Alahuhta, Janne; Hjort, Jan
Abstract: Aim: Geodiversity underpins biodiversity, but the contribution of specific geofeatures or landforms has rarely been explored. In this study, we use multiple vascular plant species diversity measures on alpha, beta and gamma levels to explore the linkage between biodiversity and co‐located landforms (e.g. gullies, dunes and lake shores). We hypothesize that biodiversity will be positively related to geodiversity, which is founded on distinct landforms. Additionally, we propose that different landforms will sustain different amounts of biodiversity and that high alpha and gamma diversity values are related to landform‐driven moisture availability whereas high beta diversity relates especially to landform‐specific microtopographic variation. Location: Rokua UNESCO Global Geopark area, Finland. Taxon: Vascular plants. Methods: We compare vascular plant species richness measures, Shannon's and Simpson's diversity indices, rarity‐weighted richness and local contribution to beta diversity at altogether three levels of biodiversity (alpha, beta and gamma) for different landforms. Landform information is compiled from aerial photos, spatial data layers and targeted field surveys. We compare results to control habitat (i.e. sites without any distinct landforms) within the study area. Results: Vascular plant diversity was higher on landforms than in control habitat. There was also notable variation between species diversity of different landforms. Moisture‐rich gullies and river shores were especially diverse at all three levels, whereas aapa mires hosted most unique species composition (highest beta diversity). Beta diversity patterns were rather comparable with alpha and gamma diversity patterns, which contradict our hypothesis. Main conclusions: This study quantitatively established a strong connection between terrestrial plant communities and multiple landforms. Our results highlighted the landform‐controlled variation in soil moisture, microclimate and microtopography in enhancing plant species diversity. Based on the results, we promote the inclusion of landform‐based geodiversity information in conservation management and in further biogeographical studies.